2020
DOI: 10.1080/08870446.2020.1745801
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity and core affects within and across days: a daily diary study

Abstract: Objective: The objective of the present study was to investigate (a) if daily physical activity at the within-person level is related to four different core affects the same evening, (b) if core affects in the evening predict physical activity the following day, and (c) if physical activity predicts core affects the following day. Design: A total of 166 university students were asked to complete the affect and physical activity measures once a day (in the evening), for seven days. Bivariate unconditional laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The average individual weekly response rate to the PANAS, OSTRC-O and exposure questionnaire was 81.6% (SD = 7.3), ranging between 71.8% and 91.9%. In total, 91% of the athletes (n = 135) reported at least one overuse injury, with an average weekly OSTRC-O severity score over the 9 weeks of 23/100 (95% CI = [22,25]). Detailed data regarding the prevalence of overuse injuries in this cohort were published elsewhere.…”
Section: Survey Response Ratementioning
confidence: 99%
See 2 more Smart Citations
“…The average individual weekly response rate to the PANAS, OSTRC-O and exposure questionnaire was 81.6% (SD = 7.3), ranging between 71.8% and 91.9%. In total, 91% of the athletes (n = 135) reported at least one overuse injury, with an average weekly OSTRC-O severity score over the 9 weeks of 23/100 (95% CI = [22,25]). Detailed data regarding the prevalence of overuse injuries in this cohort were published elsewhere.…”
Section: Survey Response Ratementioning
confidence: 99%
“…Importantly, this type of analysis examining how two different variables fluctuate rapidly in relation to themselves and to each other over time was described as a first step in a causal analysis of change, assuming that the variables are ordered in time. 21,22 More precisely, the use of withinperson analyses where both autoregressive (i.e., withinconstruct) and cross-lagged (i.e., between-constructs) effects are specified in the same model has been recently deemed as necessary; 22 it should be considered when studying the bidirectional relation affects-overuse injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study also supports previous research which has found that on days in which individuals are more active than usual they also report higher positive affect. 49,50 Previous research on MVPA and negative affect is less clear. 31 Given that negative affect had the lowest within person variability, it is possible that it was difficult to ascertain within-person relationships with MVPA or resistance training.…”
Section: Moderate-to-vigorous Physical Activity Resistance Training A...mentioning
confidence: 99%
“…Recent studies examining the role of affect in physical activity and lifestyle behaviors have used ecological momentary assessments (EMA) to capture experiences in naturalistic settings and to better understand patterns of change that occur over time (e.g., Ivarsson et al, 2020;Smith et al, 2020). In particular, a review of studies using EMA determined that higher levels of positive affect predicted greater physical activity within the next few hours and vice versa; however, the negative affect-physical activity relationship was mixed (Liao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%